A Study to Assess Pattern of Morbidities among Adolescents under School Health Program from Arural Block of North India - Bashar, Md Abu; Aggarwal, Arun Kumar; Pilania, Manju (National Journal of Community Medicine, 2017)
Introduction: Timely identification of different type of morbidities among school going adolescents under school health programme is necessary to take targeted interventions and revision of existing programmes in order to prevent them. Morbidity survey of school going adolescent is one such method. Methods: A cross sectional morbidity survey was conducted among adolescent attending two schools of a rural block of Haryana, North India with help of a structured Performa. The morbidities were identified using standard methods by trained community physicians. Results: Overall, 87.2% of the adolescents were found to have one or the other morbidity. A total of 65.8% were anaemic, 37.8% were wasted, 34.1% were stunted and 26.8% were having uncorrected refractive errors. Further, 6% of the children were found to have signs of vitamin A deficiency (VAD) in form conjunctival xerosis (3.6%) and bitot's spots (2.4%). Conclusion: Prevalence of anaemia, under nutrition and refractive errors are still quite high among adolescents despite presence of various programmes to address them. Higher prevalence of Vitamin A deficiency is alarming which requires further investigation in its cause and necessary corrective actions.